Studies on effects of static electric field exposure on liver in mice. Issue 1 (December 2018) - Lin, Qinhao; Dong, Li; Xu, Yaqian; Di, Guoqing
Abstract With the development of ultra-high-voltage direct-current transmission, the intensity of static electric field (SEF) under transmission lines increased, which has aroused public attention on its potential health effects. In order to examine effects of SEF exposure on liver, institute of cancer research mice were exposed to SEF with intensities of 27.5 kV/m, 34.7 kV/m and 56.3 kV/m, respectively. In each intensity of SEF exposure, a corresponding sham exposure group was used. Several indices relating to liver function (aspartate aminotransferase (AST) and alanine aminotransferase (ALT)) and oxidative stress (superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and malondialdehyde (MDA)) were tested after exposure of 7, 14, 21 and 35 days. Results showed that exposure to SEF with intensities of 27.5 kV/m and 34.7 kV/m for 35 days did not significantly influence any detected indices above. Under SEF exposure with intensity of 56.3 kV/m, the SOD activity in liver was significantly increased after exposure of 7 and 14 days. However, no significant increase was found in MDA content as well as the activities of AST and ALT between exposure group and sham exposure group during SEF exposure of 56.3 kV/m. It suggested that from three SEF intensities, only exposure to SEF with intensity of 56.3 kV/m (7 and 14 days) caused a temporary oxidative stress response in liver expressed by the increase in activity of SOD, but it did not produce oxidative damage. This biological effect may be related to the increase of mitochondrial membrane potential of hepatocytes caused by SEF exposure. When the membrane potential exceeds a threshold, Q cycle in mitochondria will be affected, which will result in an increase of superoxide anion concentration and ultimately an oxidative stress.